Patterns and clinical correlates of lifetime alcohol consumption in women and men with bipolar disorder: Findings from the UK Bipolar Disorder Research Network. (13th April 2020) - Gordon‐Smith, Katherine; Lewis, Katie J. S.; Vallejo Auñón, Fransico M.; Di Florio, Arianna; Perry, Amy; Craddock, Nick; Jones, Ian; Jones, Lisa
Abstract: Objectives: Despite previous literature on comorbid alcohol use disorders (AUDs) in bipolar disorder (BD), little is known about patterns of alcohol use more widely in this population. We have examined lifetime heaviest average weekly alcohol consumption levels in a large well‐characterised UK sample including lifetime clinical correlates of increasing levels of alcohol use. Methods: Participants were 1203 women and 673 men with bipolar I disorder interviewed by semi‐structured interview who had consumed alcohol regularly at any point in their life. Results: Over half of both women (52.3%) and men (73.6%) had regularly consumed over double the current UK recommended guideline for alcohol consumption. In women and men increasing levels of lifetime alcohol consumption were significantly associated with the presence of suicide attempts (women: OR 1.82, P < .001; men: OR 1.48, P = .005) and rapid cycling (women: OR 1.89, P < .001; men: OR 1.88, P < .001). In women only, increasing levels of alcohol consumption were significantly associated with more episodes of depression (OR 1.35, P < .001) and mania (OR 1.30, P < .004) per illness year, less impairment in functioning during the worst episode of mania (OR 1.02, P < .001), fewer psychiatric admissions (OR 0.51, P < .001), comorbid panic disorder (OR 2.16, P < .001) and eating disorder (OR 2.37, P < .001). Conclusions: Our results highlight the clinical importance of obtaining detailed information on levels of alcohol consumption among patients with BD. Increased levels of alcohol use, not necessarily reaching criteria for AUD, may be helpful in predicting BD illness course, in particular eating disorders comorbidity in women.